EUS-Guided FNA: Tips and Tricks - Bansal, Rinkesh Kumar; Puri, Rajesh (Journal of Digestive Endoscopy, 2020)
The development of endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) technique has been proved to be a great armamentarium to gastroenterologists and other branches including surgery, oncology, hepatology, pulmonary medicine, and internal medicine. EUS-FNA is quite safe and allows tissue acquisition from difficult anatomical locations like retroperitoneum, pancreas, and mediastinum. The current review discusses basic techniques steps of EUS-FNA including tips and tricks. Also, false negative FNA and EUS-FNA in difficult locations are discussed. We also discussed about EUS-guided fine needle biopsy.
Keywords: EUS; EUS-FNA; EUS-FNB; needle